Laser Raman and Infrared Spectra of 4-Amino-2-Chlorobenzonitrile - Rastogi, V.K.; Jain, D.K.; Sharma, Y.C. (Asian Journal of Chemistry, 2010)
Laser Raman and infrared spectrum of 4-amino-2-chlorobenzonitrile have been recorded in solid phase. The spectrum has been analysed assuming C point group for the molecule and the observed fundamentals have been assigned to different normal modes of vibration.